1968
DOI: 10.1002/ijch.196800092
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Aniline by Montmorillonite

Abstract: Sorption of aniline by montmorillonite was studied by infra‐red, X‐ray diffraction and differential thermal analysis methods. The amount of aniline sorbed and the type of bonding depend upon the interlayer cations: anilinium, H+‐ and Al3+‐ give anilinium aniline ions, NH44‐ammonium aniline ions, alkalis and alkaline earths except Cs are bonded to aniline through water bridges and transition metal cations are coordinated to aniline partly directly and partly through water bridges. Sorption does not occur in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1969
1969
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…However, with hydrogen montmorillonite, at least, direct protonation of the organic bases might be expected, by analogy with the reactions of such clays with ammonia (Fripiat, 1963) or pyridine (Farmer and Mortland, 1966). But the spectra obtained with H montmorillonite treated with ani-*The results obtained for aniline associations in this study are more accurate than those previously reported (Yariv et al, 1968) due to the more powerful grating instrument now available, which permits more accurate assessment of the positions and relative intensities of the peaks. 301 __mm--mm--mm~m~ ~"z""z"'~z~zz~zzSzz==Z"=z"-z'~=Z~~zz~zz~zz~ z~zz z=z'~ line derivatives show features similar to those of K, Na, Mg and AI montmorillonites and of type II complexes obtained with transition metals (Heller and Yariv, 1969) and differ entirely from the spectra of the corresponding anilinium or anilinium aniline samples (Fig.…”
Section: Infra-red Spectramentioning
confidence: 60%
See 3 more Smart Citations
“…However, with hydrogen montmorillonite, at least, direct protonation of the organic bases might be expected, by analogy with the reactions of such clays with ammonia (Fripiat, 1963) or pyridine (Farmer and Mortland, 1966). But the spectra obtained with H montmorillonite treated with ani-*The results obtained for aniline associations in this study are more accurate than those previously reported (Yariv et al, 1968) due to the more powerful grating instrument now available, which permits more accurate assessment of the positions and relative intensities of the peaks. 301 __mm--mm--mm~m~ ~"z""z"'~z~zz~zzSzz==Z"=z"-z'~=Z~~zz~zz~zz~ z~zz z=z'~ line derivatives show features similar to those of K, Na, Mg and AI montmorillonites and of type II complexes obtained with transition metals (Heller and Yariv, 1969) and differ entirely from the spectra of the corresponding anilinium or anilinium aniline samples (Fig.…”
Section: Infra-red Spectramentioning
confidence: 60%
“…In a previous study (Yariv et al, 1968) bands at 2625 and 2650 cm -1 were ascribed to combination bands of interlayer anilinium ions. On immersion in excess aniline, these bands turned into a broad band at 2500-2600 cm -1, which was assigned to anilinium aniline.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…No particular position was assigned to these protons. For the present study cyclohexylamine, a strong aliphatic base, and aniline, a weak aromatic one, were selected, because their reactions with montmorillonite had previously been investigated in some detail (Yariv et al, 1968;Yariv and Heller, 1970). If a sample of fresh H-montmorillonite is exposed to an organic base in molecular form, the band at about 850 cm-' is restored, very rapidly with cyclohexylamine ( Fig.…”
Section: Notesmentioning
confidence: 99%